Environmental experiments about water - Rybolt, Thomas R.; Mebane, Robert C. (Hillside, NJ, U.S.A. : Enslow Publishers, 1993)
Presents experiments that focus on the properties of water, its cycle in nature, pollution problems, and methods of purification.
Includes index.
Book Report.
Elem. School Library Collection.
Wilson's Junior High School.
5.9.
5.9
Keywords: Water -- Experiments -- Juvenile literature; Water -- Pollution -- Experiments -- Juvenile literature; Water -- Purification -- Experiments -- Juvenile literature; Acid rain -- Experiments; Experiments; Water -- Experiments; Water -- Pollution -- Experiments; Water -- Purification -- Experiments; Acid rain -- Experiments; Water pollution -- Experiments; Water -- Experiments; Water -- Purification -- Experiments